Identification and analysis of steam temperature maldistribution in superheater tubes via measured and derived parameters - Vilakazi, Lethukuthula Nokwazi (Vaal University of Technology, 2019)
Superheater and reheater heat exchangers in power plant boilers can experience temperature excursions and gradients significantly above design values due to cyclic operations. This may result in accelerated life consumption of these components. To understand better the influence of different operating conditions, research is ongoing to develop detailed thermo-fluid process models of the various boiler heat exchangers, and real-plant data are required in the validation of these models. In this study, the final superheater of a 620 MW coal-fired power plant unit was analysed based on real plant measurements taken during steady state operation at 100, 80 and 65 percent of the current boiler capacity. Process parameters routinely measured via the plant distributed control system (DCS), such as the steam temperatures, pressures and mass flow rates, were used as input data to derive other unmeasured parameters using the mass and energy balance (MEB) methodology. Thermocouples were installed previously on the inlet and outlet final superheater stub boxes as well as the outlet manifolds. Thermocouple data were collected from a data logger at the corresponding dates and times of the DCS MEB inputs. Measurement uncertainties were determined by considering instrument and statistical uncertainties, which were then propagated through the MEB calculation to the derived parameters. The MEB methodology was applied to determine the flue gas temperature and flow rates at different operating loads (65, 80 and 100 percent). The good comparison obtained between the values calculated with the MEB and those of the C-schedule for the 100 percent boiler maximum continuous rating (BMCR) provided confidence in the validity of the MEB. The MEB was also compared to real plant data of flue gas temperature. The comparison provided a difference that is less than 26℃. Identification of the measurement uncertainties provided a detailed analysis on each instrument and or measurement and how certain I could be about each measurement. Uncertainties of parameters derived using the MEB methodology were determined. This was achieved by uncertainty propagation through the MEB model. Uncertainty propagation also provided a sensitivity percentage relative to the propagated uncertainties. The extent of temperature maldistribution was determined based on the measured outside tube metal temperatures. The results from the thermocouple measurements on the steam pipes connected to the final super heater inlet and outlet manifold headers show that there is temperature maldistribution between the inlet headers of the four legs. There is also significant maldistribution at the outlet headers resulting in noticeable local temperature gradients. It can also be concluded that the low load of 65 percent resulted in the highest temperature maldistribution compared to the higher loads, of 100 and 80 percent. Super heater tube metal temperatures are exposed to high temperatures at low loads which may lead to tube leaks.
M. Tech. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Superheater; Reheater; Thermocouples; Steam temperatures; Thermocouple measurements; Temperature maldistribution; Derived parameters; Dissertations, Academic -- South Africa.; Superheaters.; Thermocouples.